Study of the landslide process in conditions of seasonally frozen soils (landslide slope of the Vorkuta river valley) - A. N. Vikhot (Vestnik MGSU)
Introduction. In view of recent trends in melting of permafrost strata, the state of cryolithozone is noted as unstable, so such exogenous geological processes as landslides are widespread.Materials and methods. The landslide process in the Vorkuta River valley near the residential area under the conditions of seasonally frozen soils was analyzed. Based on the results of vertical electrical sounding, a geoelectric section at the landslide failure edge is presented. Statistical calculations based on geodetic data, transformation of landslide displacement time series to stationary form by detrending method, correlation analysis were carried out.Results. Trends of time series on displacement points were determined. They had a quadratic distribution. All investigated series had strong determinacy. The components were checked for stationarity and distribution according to the normal law by estimation of mathematical expectations of the detrended series parameters. Short-term forecast of landslide process for one period was given by the criteria of standard quadratic regression model, the forecast graph is given. According to Kolmogorov–Smirnov criterion, the hypothesis of homogeneity of single series distribution for climatic parameters for the observation period was accepted. The correlation coefficients of the parameters of landslide scarp displacement and some climatic factors on the Chaddock scale ranged from inverse weak (–0.18) to significant (0.58) correlation.Conclusions. Two possible cases of the landslide movement were presented: passive stage and the slope flattening or the beginning of a new landslide cycle. Geodetic monitoring is necessary to establish a reliable forecast. The average annual air temperature increased slightly during the observation period. A close relationship between landslide displacements and the positive average monthly air temperature values was revealed, Kcor = 0.58. A moderate connection (Kcor = 0.5) — with the average annual precipitation. Engineering recommendations for slope stabilization are proposed: installation of heat-insulating screens to the depth of seasonal soil freezing, arrangement of drainage wells in the body of the landslide and in soils up the slope.